The value of segmentation with 2D and 3D reconstruction before vascular surgery (about a case of aortic aneurysm): Presented at the 3rd World Congress of the UNESCO Chair for Teaching and Research in Digital Anatomy Paris Descartes at Egas Moniz University Institute - Almada, Portugal. (29th March 2019) - Saidi, Mohammed; Uhl, Jean-Francois; Chahim, Maxime
Abstract : Introduction: The development of digital research at the level of the anatomy laboratory with the vascular surgery unit by anatomo-radiological interpretation based on 2D segmentation and 3D reconstruction [1 ] using serial sections of medical imaging (angiogram) for the aortic aneurysms, realizes a fundamental element in the diagnosis approach and offers a panel of tools adapted to the constraints of the clinical practice to optimize the decision of the surgical act and the restoration of the function. The objective of this study is to highlight the anatomical reports of aneurysm to improve the management of a 68-year-old patient. Materials and methods: The 256 sections of a CT angiogram of a 68-year-old patient with aortic aneurysm for exploration of chest pain. The morpho-anatomical study of the thoraco-abdominal visceral structures, as well as the posterior mediastinal region and the aneurysmal dilatations at the level of the aortic vascular axis is performed by the 3D volume rendering technique using OSIRIX® software [2 ]. Results: Interactive 3d modeling of the aorta was achieved with volume quantification of the aneurysm. Discussion and conclusion: The three-dimensional volumetric modeling of an aneurysm in a 68-year-old patient visualizes the thoraco-abdominal aortic dilatation and the importance of the aneurysm in the mediastinum on 3D reconstruction images, hence the surgical or endovascular indication and the technical management [3 ].